THE EFFECT OF OPERATIONAL RISK, WORKING CAPITAL TURNOVER, LIQUIDITY, LEVERAGE RATIO ON PROFITABILITY IN MANUFACTURING COMPANIES LISTED ON THE IDX - Fitria, Arini; Masitoh, Endang; Kurniati, Sari (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2024)
The purpose of this research is to analyze the factors that influence the profitability of a manufacturing company listed on the IDX for the 2019-2021 period. Sampling in this study using purposive sampling. There were 81 companies that were used as samples in this study which had met the sampling criteria. The data analysis technique uses multiple linear analysis. The results of this study indicate that operational risk and working capital turnover have no effect on profitability. While liquidity and leverage ratio affect profitability.